Unique Versus Redundant Functions of IL-1α and IL-1β in the Tumor Microenvironment - Voronov, Elena; Dotan, Shahar; Krelin, Yakov; Song, Xiaoping; Elkabets, Moshe; Carmi, Yaron; Rider, Peleg; Cohen, Idan; Romzova, Marianna; Kaplanov, Irena; Apte, Ron N. (Frontiers in Immunology, 2013)
Interleukin-1 (IL-1) is a major “alarm” upstream pro-inflammatory cytokine that also affects immunity and hematopoiesis by inducing cytokine cascades. In the tumor arena, IL-1 is produced by malignant or microenvironment cells. As a pleiotropic cytokine, IL-1 is involved in tumorigenesis and tumor invasiveness, but also in the control of anti-tumor immunity. IL-1α and IL-1β are the major agonists of IL-1, while IL-1Ra is a physiological inhibitor of pre-formed IL-1. In their secreted form, IL-1α and IL-1β bind to the same receptors and induce the same biological functions, but IL-1α and IL-1β differ in their compartmentalization within the producing cell or the microenvironment. IL-1β is only active in its processed secreted form and mediates inflammation, which promotes carcinogenesis, tumor invasiveness and immunosuppression, whereas IL-1α is mainly cell-associated and in the tumor contest, when expressed on the cell membrane, it stimulates anti-tumor cell immunity manifested by tumor regression. It the tumor milieu, extracellular level of IL-1α is usually low and do not stimulate broad inflammation that promotes progression. Immunosuppression induced by IL-1β in the tumor microenvironment, mainly through MDSC induction, usually inhibits or masks anti-tumor cell immunity induced by cell-associated IL-1α. However, in different tumor systems, redundant or unique patterns of IL-1α and IL-1β expression and function have been observed. Recent breakthroughs in inflammasome biology and IL-1β processing/secretion have spurred the development of novel anti-IL-1 agents, which are being used in clinical trials in patients with diverse inflammatory diseases. Better understanding of the integrative role of IL-1α and IL-1β in distinct malignancies, will enable the application of novel IL-1 modulation approaches at the bedside, in cancer patients with minimal residual disease (MRD), as an adjunct to conventional approaches to reduce the tumor burden.